Modeling And Theoretical Characterization Of Circular pMUT For Immersion Applications. - Yaacob, Mohd Ikhwan Hadi; Arshad, Mohd Rizal; Manaf, Asrulnizam Abd (2010)

(untitled)
This paper reported modeling and theoretical characterization of circular piezoelectric micromachined ultrasonic transducer (pMUT) for immersion applications.